How Social Welfare Program, Transparency and Accountability of Rural Funding Management Enhancing the Public Welfare - Simamora, Lestarina; Pane, Aditya Amanda; Dalimunthe, Hasbiana (PT. Riset Press International, 2024)
Public welfare is a concern that the government continues to resolve. The government has undertaken various efforts to improve public welfare. This research aims to determine the influence of goverment social welfare programs known as family hope program (PKH), transparancy and accountability of rural funding management on public walfare in Gaya Jaya Village, Lawe Sigala Gala District, Southeast Aceh. The population used in this research is the citizens of Gaya Jaya Village, Lawe Sigala-Gala District, Southeast Aceh who obtaining grants from government social walfare program (PKH). The whole population of this research is used as a sample. The number of samples used in this research amounted to 41 respondents. This research data is primary data obtained from research questionnaires, distributed to all respondents. The results of this research show that the goverment social welfare programs, transparency and accountability of rural funding management have positive and significant effect on public walfare in Gaya Jaya Village, Lawe Sigala Gala District, Southeast Aceh. From the results of this research, it is expected that in the next government social welfare program there will be no mistargeting in assisting the public.